Potency of Yeasts to Promote Induced Resistance on Chili Plant (Capsicum annuum L.) against Yellow Leaf Curl Disease - Sri Hartati; Rika Meliansyah; Luciana Djaya; Ceppy Nasahi; Ramadhan Kamal Putra (Jurnal Perlindungan Tanaman Indonesia, 2020)
Yellow leaf curl is a major disease on chili plants. The use of antagonistic yeasts as the control agents is a good alternative in  an environmentally friendly control method. This study was objected to evaluate the potencies of Rhodotorula minuta and Candida tropicalis to promote induced resistance on chili plants against yellow leaf curl disease. The experiment was arranged in the randomized complete block design with 9 treatments and 3 replications. The treatments were the application of the yeasts at three different times of virus inoculation, as follows: A. R. minuta, virus inoculation at 3 days after transplanting (dat), B. R. minuta, virus inoculation at 7 dat, C. R. minuta, virus inoculation at 10 dat, D. C. tropicalis, virus inoculation at 3 dat, E. C. tropicalis, virus inoculation at 7 dat, F. C. tropicalis, virus inoculation at 10 dat, G. control, virus inoculation at 3 dat, H. control, virus inoculation at 7 dat, and I. control, virus inoculation at 10 dat. No treatment was applied to the control.  The yeasts were applied by soaking the chili seeds, and pouring the suspension into the growth media at transplanting. The variables observed were incubation period, disease severity, and disease incidence. Peroxidase activity, phenylalanine ammonia lyase activity, and salicylic acid accumulation were also analyzed. The results showed that the application of R. minuta or C. tropicalis was able to extend the disease incubation period, but did not reduce the yellow leaf curl disease incidence and severity. The treatment of R. minuta, virus inoculation at 7 dat, increased the peroxidase activity from 2590.80 units to 6870.93 units (0.5 minute) and from 577.367 units to 1131.300 units (2.5 minutes), PAL activity from 16.059 to 17.911 A290/mg, and accumulation of salicylic acid from 2.785 to 6.263 ppm. Application of C. tropicalis, virus inoculation at 7 dat, increased the peroxidase activity from 2590.80 units to 6033.067 units (0.5 minute) and from 577.367 units to 950.967 units (2.5 minutes), and accumulation of salicylic acid from 2.785 to 6.982 ppm.